Rigor versus vigor: Some dubious issues in the debate on research philosophy - Kerman, Herbert C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Many dubious issues turn on one or another aspect o f what might be cailed the "rigor vs. vigor ” controversy. They are generally " false issues” of questionable validity, such as naturalistic v s. experimental, psychological vs. sociological, quantitative vs. qualitative, and holistic or molar vs. elementalistic or reductive approaches. The real issue is whether a particular approach is appropriate to the question the investigator is trying to answer, and the even m ore complicated matter of whether the question is worth asking. Rigor, the stressing o f hard facts through the use o f exact method s is contrasted with vigor, stressing methods that will capture real-life flavor in all its fullness, and this d dichotomy y is used to illustrate that the choice o f a proper method depends on the nature of the problem under investigation, the stage of development o f the research area, the specific problem on which the work is being done, and the preferred style of the investigator. The value o f the research depends upon h o w systematic and imaginative the approach is, for n o experimental finding in our field can stand meaningfully by itself, apart from the conceptual thinking and related theory, or apart from cumulative supportive evidence.